Tumors and biofilms: too much coincidences to be casual - Verevka, S.V.; Voroshylova, N.M. (Вiopolymers and Cell, 2018)
The existence of the majority of microorganisms in the form of three-dimensional associates on the phase interface proves the significant survivable advantages of such form of life at compare with monocellular planktonic ones. These advantages provided to biofilms a place of the most widely distributed form of life if not the dominative one. There is a strong similarity in properties of biofilms and malignant tumors that promotes considering the latter as some kind of biofilms. Such point of view facilitates understanding some features of carcinogenesis as well as the grounds for perspective directions in the prevention of metastases. Існування більшості мікроорганізмів у формі тривимірних асоціатів на межі розподілу фаз свідчить про її значні переваги такої для виживання, порівняно з дисперсною формою, та дозволяє визначити біоплівки як домінуючу форму життя. Спостерігається виражена подібність багатьох властивостей біоплівок та злоякісних пухлин, що дозволяє провести певну аналогію між ними. Подібний погляд полегшує розуміння окремих рис карциногенеза та створює передумови для обґрунтування перспективних напрямків попередження метастазування. Существование большинства микроорганизмов в форме трехмерных ассоциатов на границе раздела фаз свидетельствует о значительных преимуществах для выживания по сравнению с дисперсным существованием, что позволяет определить биопленки как доминирующую форму жизни. Наблюдается выраженное подобие множества свойств биопленок и злокачественных опухолей, что позволяет провести определенную аналогию между ними. Подобный взгляд облегчает понимание отдельных черт карциногенеза и создает предпосылки для обоснования перспективных направлений предупреждения метастазирования.